(3GdCWaGd GdeJhGLOhf hGdYGedhf aj GdThGQY aj dHfGf(B: (3NUGFU hMLes - (3eDSSI GdHMhK hGdESJTGQGJs ((3HjQhJs (3hRGQI GdYed GddHfGfjI (B/ (3efXeI GdYed GdOhdjI (B/ (3LeYjI EfbGP GdWad (B/ (3GdjhfjSas, 2015)
(3jgOa gPG GdJbQjQ Edi hVY hJfajP HQfGemL NGU dJbOjQ MLe XGgQI Yed GdCWaGd hecGaMJgG Vef GdEWGQ GdTGed dNWI GdYed GdhWfjI ddbVGA Ydi CShC CTcGd Yed GdCWaGd aj dHfGf, ceG jSYi Edi JMOjO GdNUGFU GdeNJdaI dgDdGA GdCWaGd, hPdc HZjI SMH CcHQ YOO eecf ef GdCWaGd ef GdTGQY(B. (3ceG jgOa Edi JRhjO GdMcheI GddHfGfjI hGdefXeGJ ZjQ GdMchejI HHMhmK bGFeI Ydi GdCOdI Mhd MLe hNUGFU GdCWaGd GdPjf jYjThf Ch jYedhf aj ThGQY dHfGf, hMhd hVYge GdGLJeGYj hGdGbJUGOj(B. (3TedJ GdefgLjI GdeYJeOI OQGSI (B700 (3MGdI dCWaGd dHfGfjjf hZjQ dHfGfjjf aj GdThGQY, ehRYjf Ydi (B18 (3bVGA ef GdaFI GdYeQjI (B(5 (3Edi (B17(3SfI(B). (3Je GdGYJeGO Ydi GdebGHdI, eY aYGdjGJ eYfjI HbVGjG GdCWaGd, dJLejY GdeYdheGJ hYdi OQGSGJ hJbGQjQ hGdCfXeI GddHfGfjI hGdehGKjb hGdEJaGbjGJ GdOhdjI ddCee GdeJMOI hefXeI GdYed GdOhdjI, cPdc GYJeO Ydi OQGSI MGdI dCgd CWaGd GdThGQY hddCWaGd GdefNQWjf aj fTGWGJ ZjQ eTQhYI(B. (3HjfJ GdfJGFL CQHYI YhGed QFjSjI JDOj dYjT Ch Yed GdCWaGd aj ThGQY dHfGf, hgj GdGSJHYGO GdGLJeGYj, gTGTI hVY GdCSQI, JOab GddGLFjf GdShQjjf Edi dHfGf, GdLQjeI GdefXeI hGSJZdGd GdCWaGd(B. (3ceG hCXgQJ GdfJGFL Cf KdKj GdCWaGd aj GdThGQY aj dHfGf ge ef GdaJjGf, JJQGhM CYeGQ CcKQ ef fUage Hjf (B10 (3h(B14 (3YGkeG, CcKQge jYedhf CcKQ ef (B6 (3CjGe aj GdCSHhY, h(B8 (3SGYGJ hfUa GdSGYI aj GdeJhSW jhejG, hCf (B73% (3efge ge ShQjhf, jeGQShf CfTWI EbJUGOjI eJfhYI Ydi QCSgG egfI GdJSqhd, dGaJkI Edi Cf GdZGdHjI GdYXei ef GdCWaGd GdPjf jYjThf Ch jYedhf aj GdThGQY YKQ Ydjge aj GdeOf, NGUI aj HjQhJ hWQGHdS(B.s
(3GdfhY (B: (3JbQjQs
Keywords: Child Labor; Travail des enfants; (3YeGdI GdGWaGd hCWaGd GdThGQYs